Protein Content Analysis of Protease Enzymes Extracted from Ficus Species and Papaya Using Qubit Fluorometer - Ismed, Ismed; Yenrina, Rina; Hasbullah, Hasbullah; Syukri, Daimon; Yusniwati, Yusniwati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to quantify the protein content in crude ficin enzymes obtained from the fruit and latex of various Ficus species and Papaya. This research has been encouraged by the considerable potential of these enzymes in different biotechnological applications, while data with regard to the protein content of these enzymes is limited. This study used a quantitative approach using qubit fluorometer to quantify the protein content in crude enzymes derived from the fruit and latex of these plants. Based on results, the protein content in crude ficin enzymes, two types of research obtained from Ficus aurata (Miq.) fruit was 0.92µg/ml and from papaya fruit as 3.16 µg/ml. For latex, it was observed that the protein content in crude ficin enzymes was determined as 6.14 µg/ml for Ficus aurata (Miq.), 2.58 µg/ml for Ficus racemosa L., and 5,27 µg/ml for Ficus padana Burm.f.. The protein content from papaya latex was 15,98 µg/ml. These findings show the differences in the protein content of the enzymes obtained from different species of Ficus and Papaya as a basis for further study on using these enzymes for biotechnological purposes.